Xenophon's Psychology of philotimía - Illarraga, Rodrigo José (2020)
In this brief paper I intend to present an overview on the notion of philotimía in Xenophon. I will argue that Xenophon distinguishes between two types of philotimía false and corrupt philotimía, and good true philotimía and that sophrosúne is what sets them apart.